2018
DOI: 10.1186/s40409-018-0170-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and inflammatory potential of a phospholipase A2 from Bothrops jararaca snake venom

Abstract: BackgroundSnake venom phospholipases A2 (PLA2s) have been reported to induce myotoxic, neurotoxic, hemolytic, edematogenic, cytotoxic and proinflammatory effects. This work aimed at the isolation and functional characterization of a PLA2 isolated from Bothrops jararaca venom, named BJ-PLA2-I.Methods and ResultsFor its purification, three consecutive chromatographic steps were used (Sephacryl S-200, Source 15Q and Mono Q 5/50 GL). BJ-PLA2-I showed acidic characteristics, with pI~ 4.4 and molecular mass of 14.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 60 publications
0
18
0
5
Order By: Relevance
“…Boeno et al [ 90 ] have shown that purified Lys49-PLA2 homologue from Bothrops jararacussu might contribute to inflammasome formation through the activation of NLRP3, which in turn interacts with caspase-1, leading to an inflammatory response via IL-1β. PLA2 mediated inflammatory response was observed by Cedro et al [ 91 ]. Using purified Asp49-PLA2 (5, 10 and 20 μg/mL) from Bothrops jararaca snake venom, an increased level of IL-6, IL-1β and PGE2 was described through neutrophil stimulation, although its cytotoxic activity is inferior to those observed in case of the Lys49-PLA2 homologue structure.…”
Section: Discussionmentioning
confidence: 93%
“…Boeno et al [ 90 ] have shown that purified Lys49-PLA2 homologue from Bothrops jararacussu might contribute to inflammasome formation through the activation of NLRP3, which in turn interacts with caspase-1, leading to an inflammatory response via IL-1β. PLA2 mediated inflammatory response was observed by Cedro et al [ 91 ]. Using purified Asp49-PLA2 (5, 10 and 20 μg/mL) from Bothrops jararaca snake venom, an increased level of IL-6, IL-1β and PGE2 was described through neutrophil stimulation, although its cytotoxic activity is inferior to those observed in case of the Lys49-PLA2 homologue structure.…”
Section: Discussionmentioning
confidence: 93%
“…Other reports show the use of up to three stages, such as studies involving the species Bothrops atrox and Bothrops jararaca, which were subjected to different stages and buffers. The other purifications mentioned were the use of a C18 column in the RP-HPLC stage, differing only from BE-I-PLA 2 isolated from B. erythromelas [34,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…PLA 2 hydrolyses fatty acids at the sn-2 position of membrane phospholipids releasing lysophospholipids and arachidonic acid (Cedro et al 2018). Arachidonic acid in turn leads to the production of eicosanoids such as prostaglandins, thromboxanes and leukotrienes (Yui et al 2015), which are mediators of inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%